Museum DoorDacht : Elke Krystufek, Julião Sarmento, Valerius De Saedeleer, Albert Oehlen, Marc Goethals. - De Clercq, Anouk; Bryans, Matt; Vanderleenen, Marc; Maheo, Erwan; Museum Dhondt-Dhaenens, Deurle (Deurle : Museum Dhondt-Dhaenens, 2006)
Krystufek, Elke ; Sarmento, Julião ; De Saedeleer, Valerius ; Oehlen, Albert ; Goethals, Marc
Tentoonstellingen en projecten van afgelopen 6 maanden in MDD Deurle, 2006.
boek